Relationship Between Language, Excecutive Functions and Metacognition - Rodríguez Ortiz, Angélica María (2024)
This article reflects on the role of language in higher-order thought processes carried out by executive functions, especially those involved in metacognitive regulation. The investigation was intended to reveal the relationships between language and executive functions that are carried out by metacognitive regulation processes, since, for some theorists, language is taken as a product and not as a constituent element of higher-level thought processes. To this end, the relations between language and thought were analyzed; subsequently, the relations between executive functions and metacognitive regulation were examined, supporting the argument that language is a structuring foundation of thought and a sine qua non-condition for the existence of executive function processes involved in metacognitive regulation.